Escribir la historia de México colonial con herramientas digitales: medios digitales, experiencias y debates - Isabel M. Povea Moreno; Ricardo A. Fagoaga Hernández (Mélanges de la Casa de Velázquez, 2017)
Little by little historians are including digital technologies into their scholarship. In this article, first, we pay attention to the use of digital media (manuscript and bibliographic repositories, blogs, social networks, etc.) when researching, writing and sharing history. Second, we analyze the impact of digital experiences in historical, cultural and/or environmental discussions.